Мәдениет құндылықтары: зерттеу тұжырымдамасы және әдістері - Abdulina, N.; Tarasti, E. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2019)
Having studied the basic theoretical approaches to the study of values, the authors came to the conclusion that there are various theories and approaches with their shortcomings, as well as important innovative provisions. The main objective of the article is to find a compromise between these theories, use them in practice and contribute to the study of values. The subject of the research is the most important methodological directions of the theory. The result was the isolation and theoretical justification of the application of these methods in science. A new methodology has been developed for studying sociocultural trends in social development, in particular, the transformation of the spiritual values of the Kazakhstani generation-Y society. It should be emphasized that the problem of the transformation of human values is very relevant for Kazakh culture at present and is the core of culture, because in the context of globalization, the main problems of spirituality remain in the shadow, and the market system (competitiveness and money) replaces all values and becomes the center of existence and essence modern man. The article can become the basis for developing a new original methodology for studying and determining the direction in the study of the phenomenon of value. Key words: values, Kazakh culture, transformation, research methods and globalization.